Early Detection of Non-Communicable Diseases through Health Checks and Health Education in the Community of Tebing Tinggi Okurang Village, Rumbai Timur District, Pekanbaru City - Amelia Ami; Putri Alifa Sapruddin; Dhea Indra; Sri Dewi; Hamisa Andreyanti; Nuraliza Nuraliza; Rahma Shelfana; Kamilah Hayati; Evi Nurul Khalifah; Aulia Rahmadhani; Abi Wahyudi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Non-Communicable Diseases (NCDs) are a major cause of morbidity and mortality worldwide, including in Indonesia. Low public awareness of the importance of regular health checks and adopting a healthy lifestyle increases the risk of NCD complications. The area is also starting to develop into a tourism destination, necessitating solutions to boost the economy. This community service activity aims to conduct early detection of NCDs through health checks and dishwashing soap making training for the community in Tebing Tinggi Okura Village to boost the economy. The methods used included observation, dishwashing soap making training, and blood pressure, blood sugar, uric acid, and weight checks on 34 respondents. The results showed that most respondents had normal test results, but 47.06% of respondents had above-normal blood pressure, 20.58% had blood sugar levels categorized as prediabetes to diabetes, and 32.35% had high uric acid levels. These findings indicate a significant risk of hypertension, diabetes mellitus, and hyperuricemia in the productive age group. Early detection has proven crucial for preventing NCDs through regular health checks. This program emphasizes the importance of promotional and preventive efforts to reduce the incidence of NCDs at the community level. Training in making marketable dishwashing soap significantly helps communities reduce expenses and boosts the economy.